Reception of the delegates by socialist officers and soldiers in the Arcadenhof of the town hall. The foreign delegates are sitting; behind them, standing for the soldiers, is Adler
Reception of the delegates by socialist officers and soldiers in the Arcadenhof of the town hall. The foreign delegates are sitting; behind them, standing for the soldiers, is Adler.